BUDAYAKEMISKINAN NELAYAN DI MANGUNHARJO SEMARANG - Setyorini, Heny Budi (Sabda: Jurnal Kajian Kebudayaan, 2013)
Mangunharjo is an isolated area located in Northern Coast of Java. where most residents are fishermen. There are various dimensions of poverty of the residents, among others are social, economic cultural and institutional. Several factors which contribute to She poverty are natural conditions, technology (fishing gears), education level, pattern of life, marketing and government programs which do not favor them. There are four integrations to solve this problem namely infersectors, expertise and knowledge, multi problem solving and also location integration.